Genomics and proteomics: functional and computational aspects - Suhai, Sándor (Kluwer Academic Publishers, 2002)
... and Counting -- Obtaining and Evaluating Gene Expression Profiles with cDNA Microarrays -- Large Scale Expression Screening Identifies Molecular Pathways and Predicts Gene function -- The Glean Machine -- Automatic Assembly and Editing of Genomic Data -- Quest -- An Essay on Individual Sequence Variation in Expressed Sequence Tags(ESTs) -- Sequence Similarity Based Gene Prediction -- Functional Proteomics -- The Genome as a Flexible Polymer Chain -- Analysis of Chromosome Territory Architecture in the Human Cell Nucleus -- From Sequence to Structure and Function -- Shox Homeobox Gene and Turner Syndrome -- A Feature-Based Approach to Discrimination and Prediction of Protein Folding -- Linking Structural Biology With Genome Research -- G Protein-Coupled Receptors, or The Power of Data -- Distributed Application Management in Bioinformatics -- Is Human Genetics Becoming Dagerous to Society?.